Electrochemical sensing platform for simultaneous detection of 6-mercaptopurine and 6-thioguanine using RGO-Cu2O/Fe2O3 modified screen-printed graphite electrode - Fatemeh Irannezhad (International Association of Physical Chemists (IAPC), 2021)
A sensitive electrochemical sensor was developed using reduced graphene oxide RGO-Cu2O/Fe2O3 nanocomposite for 6-mercaptopurine detection based on a facile fabrication method. The surface morphology and structural composition of this nanocomposite was evaluated by X-ray diffraction (XRD), field emission scanning electron microscopy (FE-SEM), and Fourier transform infrared (FT-IR) spectroscopy. The screen-printed graphite electrode (SPGE) modified with RGO-Cu2O/Fe2O3 nanocomposite (RGO-Cu2O/Fe2O3/SPGE) indicated excellent electrochemical properties to detect 6-mercaptopurine. The linear dynamic range was estimated between 0.05 and 400.0 μM for 6-mercaptopurine detection, with a limit of detection of 0.03 μM. Also, RGO-Cu2O/Fe2O3/SPGE sensor showed good activity for simultaneous detection of 6-mercaptopurine and 6-thioguanine. In the coexistence system of 6-mercaptopurine and 6-thioguanine, two clear and well-isolated voltammetric peaks were obtained by differential pulse voltammetry (DPV). Additionally, the proposed sensor was examined for applicability by determining 6-mercaptopurine and 6-thioguanine in real samples, and the recovery in the range of 97.5-103.0 % was obtained.